Eligibility of patients with type 2 diabetes for sodium‐glucose co‐transporter‐2 inhibitor cardiovascular outcomes trials: An assessment using the Diabetes Collaborative Registry. Issue 8 (24th April 2019) - Wittbrodt, Eric; Chamberlain, David; Arnold, Suzanne V.; Tang, Fengming; Kosiborod, Mikhail
Abstract: Generalizability of findings from cardiovascular outcomes trials (CVOTs) to patients with type 2 diabetes (T2D) in clinical practice is unknown. We assessed the proportions of patients in the Diabetes Collaborative Registry who would have met enrolment criteria for pivotal CVOTs of sodium‐glucose co‐transporter‐2 inhibitors (SGLT‐2is): EMPA‐REG OUTCOME, CANVAS, DECLARE and VERTIS CV. In 172 643 patients, mean [standard deviation (SD)] age and HbA1c were 68.1 (11.8) years and 7.8% (2.2), respectively; 56.8% of patients were men and SGLT‐2i use was 4.4%. Atherosclerotic cardiovascular disease (ASCVD) prevalence was 64.3% and mean 10‐year ASCVD risk was 28.6% in patients without ASCVD. Proportions of patients eligible for CVOTs ranged from 26% (EMPA‐REG OUTCOME) to 44% (DECLARE); 48% of patients were ineligible for all CVOTs. Mean (SD) ASCVD risk was 25.4% (22.6), 32.1% (20.6) and 37.7% (19.4) in patients eligible for no, one or two CVOTs, respectively. SGLT‐2i use was low in patients eligible for no CVOTs (3.5%) and at least one CVOT (5.2%). In conclusion, applicability of CVOT results to patients with T2D in clinical practice varies based on trial eligibility criteria.